Pengambilan Keputusan Pembelian Produk berdasarkan Ekuitas Merek - Rahayu Mardikaningsih; Arif Rachman Putra (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2021)
Brand equity is a manifestation of the strength of a brand and is an important contributor to influencing and directing consumer behavior towards the purchasing decision-making process. A high level of brand equity presents a high opportunity for consumers to choose from. This type of research used in this research is explanatory research methods. This study intends to explain the relationship in the form of the influence of independent variables on the dependent variable. The sampling method uses accidental sampling technique. With 100 respondents set. The conditions set as respondents are people who have bought Bango soy sauce. The research area was conducted in the city of Surabaya. The purpose of this study is to determine the forming variables of brand equity have a significant influence on consumer behavior in determining the purchasing decision of Bango soy sauce. The results showed that brand awareness had a significant effect on purchasing decisions; brand associations significantly influence purchasing decisions; perceived quality has a significant effect on purchasing decisions; brand loyalty has a significant effect on purchasing decisions; and brand equity has a significant effect on purchasing decisions.